Overview of Puskesmas Leadership Understanding Coordination of Care Functions in Decline Non-Communicable Diseases (NCD) in the Work Area - Dian Amalia Azka (HM Publisher, 2021)
The Description of the head of local government clinic leadership understanding through the coordination of healths ervice Function In Decreasing Non Communicable Diseases (NCD) In the Working Area. Non-communicable diseases (NCD) such as heart and blood vessel disease, Diabetes Mellitus (DM), chronic lung disease, cancer (especially cervical and breast cancer) are among the health concerns of national and global concerns. To reduce the number of NCD required first-level health facilities in this case is the Puskesmas that can be the implementation of gatekeeper concept with the strengthening of four primary function of primary services, one of which is the coordination function. Therefore, it is necessary for leaders of puskesmas who have a good understanding of the coordination of care function to decrease NCD. This study aims to determine the description of the leadership of the puskesmas through the coordination of health in the decrease of Non Communicable Diseases (NCD) in its working area. This study is a descriptive study with cross sectional design, with a total sample of 37 respondents. The data were collected using questionnaires that have been tested for validity and reliability. Measurement results can be grouped into 3 categories of knowledge; ie good (if score 76% -100%), enough (56-75%), and less (<= 55%). From the results of the study, all respondents (37 respondents) had a total score above 76%, it can be concluded that the leaders of Puskesmas in Palembang City have a good understanding about the function of health coordination service in decreasing NCD in their working area.